THE EVOLUTION OF THE KOREAN LANGUAGE UNDER THE INFLUENCE OF SOCIAL MEDIA AND INTERNET CULTURE - Akramova Shokhsanam Isomiddin qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article examines the evolution of the Korean language under the influence of social media and internet culture. It explores how digital communication platforms have facilitated the emergence of new slang, abbreviations, and linguistic trends. The impact of English loanwords, Konglish expressions, and the increasing informalization of language are discussed in detail. Additionally, the article highlights the role of hashtags, viral expressions, and the potential future developments of the Korean language in the digital age. By analyzing these trends, the study provides insight into how modern technology continues to reshape linguistic practices in Korea.